The complete chloroplast genome sequence of Distylium macrophyllum (Hamamelidaceae). Issue 1 (2nd January 2020) - Chen, Shuifei; Li, Yao; Wang, Lu; Xie, Lei; Ge, Xiaomin; Zhou, Xu; Hu, Yaping; Zhang, Wenwen; Fang, Yanming; Ding, Hui
Abstract: Distylium macrophyllum H.T.Chang is a critically endangered tree species endemic to southern China. In this study, we assembled and characterized the plastome of D. macrophyllum using Illumina paired-end data. The circular genome is 159, 089 bp in size, consisting of two copies of inverted repeat (IR) regions of 26, 235 bp, one large single-copy (LSC) region of 87, 822 bp, and one small single-copy (SSC) region of 18, 797 bp. It encodes a total of 114 unique genes, including 80 protein-coding genes, 30 tRNA genes, and four rRNA genes. Phylogenetic analysis based on 13 cp genome sequences indicated that D. macrophyllum was sister to the clade of D. tsiangii and Parrotia subaequalis .